Narrativas orais na comunidade do Julião - Saboia, Cínthia Bastos (2016)
The oral narrative comes from ancient times and was propagated in various places and it was transmitted from generation to generation through oral narrators, by voice, body and performance. Teaching values and beliefs, inspiring fear and causing comicity, it’s part of the people’s culture. The first Portuguese who came to Brazil have shown interest in the customs, ways of life of people who lived here, the Indians, and since then observations and descriptions were made, collections of their stories, and scholars prepared translations in various periods. This work aims to contribute to this research area by collecting narratives of a riverside community in the Amazon, the Julião’s Community. Therefore, we carried out interviews, which allowed collecting various information and narratives. Based on these data, we gathered several community’s cultural aspects, including part of its history and settlement - which are not yet registered in books. We also analyzed and interpreted a group of thirteen narratives about the “boto” and eleven about the “giant anaconda”, which, along with other narratives found, were recorded in audio and video with an approximate duration of 50 min. It was also possible to study aspects of the oral narratives and the community’s current social situation. Keywords: Amazon. Riverside community. Oral narrative. Oral narrator.